Akuntabilitas Pengelolaan Dana Desa: - Rahmi Kurnia; Nurzi Sebrina; Halmawati Halmawati (Universitas Negeri Padang, 2019)
This study aims to find out how the accountability of Village Fund management includes planning, implementation, administration, reporting and accountability in the Luhak Nan Duo District of West Pasaman District, West Sumatra Province. The research method use is a qualitative research method with a descriptive type. Data sources are primary data and secondary data. Data collection techniques are carried out by observation, interviews, and documentation. The triangulation method is used in testing the validity or credibility of data. The type of triangulation used is source triangulation because the data obtained is data from various sources. The results showed: (1) Planning has implemented the principle of participation and transparency, but the preparation of Village Fund planning and Village Budget is not in accordance with the time set in Pemendagri Number 113 of 2014 concerning Village Financial Management article 20 due to delays (2) Implementation has implemented the principle of transparency and participation, and accountability principles have not been fully carried out by the activity management team (TPK) because of the delay in reporting activities, but from the Village Government has implemented the principle of accountability related to revenue and expenditure in accordance with Permendagri Number 113 of 2014 concerning Village Financial Management article 24 (3) Administration has applied the principle of accountability (4) Reporting and accountability has applied the principle of accountability and transparency, but reporting and accountability of APBD Village